Applications of an Analytical Framework for the Study of the Social Construction of Target Groups in Policy Design - Rave Restrepo, Juan Camilo (Revista del CLAD Reforma y Democracia, 2020)
This article presents an explanation about Helen Ingram and Anne Schneider´s analytical framework and discusses trends in an empirical research where public policy is the subject of analysis. To this end, an analysis of 75 Anglophone bibliographic references between 1993 and 2020 was carried out, using eight (8) criteria for documentary review. Three (3) results stand out: omission of explicit causality arguments to attune the framework to the research intentions, ambiguity in the instrumentalization of the proposal as a “framework or theory”, and plurality in the use of ideal types as descriptive categories of the position of target groups.